Spatial multiomic profiling reveals the novel polarization of foamy macrophages within necrotic granulomatous lesions developed in lungs of C3HeB/FeJ mice infected with Mycobacterium tuberculosis - Seto, Shintaro; Nakamura, Hajime; Guo, Tz-Chun; Hikichi, Haruka; Wakabayashi, Keiko; Miyabayashi, Akiko; Nagata, Toshi; Hijikata, Minako; Keicho, Naoto (Frontiers in Cellular and Infection Microbiology, 2022)
Infection with Mycobacterium tuberculosis leads to the development of tuberculosis (TB) with the formation of granulomatous lesions. Foamy macrophages (FM) are a hallmark of TB granulomas, because they provide the primary platform of M. tuberculosis proliferation and the main source of caseous necrosis. In this study, we applied spatial multiomic profiling to identify the signatures of FM within the necrotic granulomas developed in a mouse model resembling human TB histopathology. C3HeB/FeJ mice were infected with M. tuberculosis to induce the formation of necrotic granulomas in the lungs. Using laser microdissection, necrotic granulomas were fractionated into three distinct regions, including the central caseous necrosis, the rim containing FM, and the peripheral layer of macrophages and lymphocytes, and subjected to proteomic and transcriptomic analyses. Comparison of proteomic and transcriptomic analyses of three distinct granulomatous regions revealed that four proteins/genes are commonly enriched in the rim region. Immunohistochemistry confirmed the localization of identified signatures to the rim of necrotic granulomas. We also investigated the localization of the representative markers for M1 macrophages in granulomas because the signatures of the rim included M2 macrophage markers. The localization of both macrophage markers suggests that FM in necrotic granulomas possessed the features of M1 or M2 macrophages. Gene set enrichment analysis of transcriptomic profiling revealed the upregulation of genes related to M2 macrophage activation and mTORC1 signaling in the rim. These results will provide new insights into the process of FM biogenesis, leading to further understanding of the pathophysiology of TB granulomas.